Lysinibacillus antri sp. nov., isolated from cave soil. Issue 5 (24th April 2020) - Narsing Rao, Manik Prabhu; Dong, Zhou-Yan; Niu, Xue-Ke; Zhang, Kun; Kang, Ying-Qian; Dhulappa, Awalagaway; Xiao, Min; Li, Wen-Jun
Abstract : A Gram-stain-positive, motile, rod-shaped and endospore-forming strain, SYSU K30002 T, was isolated from a soil sample collected from a karst cave in Xingyi county, Guizhou province, south-west China. SYSU K30002 T grew at 28–40 °C (optimum, 37 °C), at pH 5.0–8.0 (optimum, pH 7.0) and in the presence of 0–4 % (w/v) NaCl (optimum in the absence of NaCl). The cell-wall peptidoglycan type was A4 α (Lys–Asp). The cell-wall sugars of SYSU K30002 T were ribose, galactose and mannose, and MK-7 was the menaquinone. The major fatty acids were iso-C15 : 0, C16 : 1 ω 7 c alcohol and iso-C16 : 0 . The polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and two unidentified phospholipids. The G+C content of the genomic DNA was 36.1 mol%. The average nucleotide identity values between SYSU K30002 T and its closest relatives were below the cut-off level (95–96 %) for species delineation. Based on phenotypic, chemotaxonomic and genome comparisons, strain SYSU K30002 T represents a novel species of the genus Lysinibacillus, for which the name Lysinibacillusantri sp. nov. is proposed. The type strain is SYSU K30002 T (=KCTC 33955 T =CGMCC 1.13504 T ).